Assessing the Consistency of Reporting for E-Cigarette Brand, Device Type, and Flavor in the National Youth Tobacco Survey: Implications for Regulatory Decision-Making - Rohay Jeffrey M.; Curtin Geoffrey M.; Pillitteri Janine L.; Gerlach Karen K. (Contributions to Tobacco and Nicotine Research)
The National Youth Tobacco Survey (NYTS) collects self-reported data from U.S. middle and high school students on past-30-day e-cigarette use, including device type used most often, all flavors used, and all brands used. These data are central to regulatory decision-making by the U.S. Food and Drug Administration (FDA) when assessing the population-level risks of e-cigarettes, which underscores the importance of verifying that estimates from the survey are accurate. The current analyses assessed the 2023 and 2022 NYTS estimates of youth e-cigarette use to examine whether the reported brand used is consistent with the reported device type and flavors used among past-30-day only brand and usual brand users of Vuse, JUUL, Elf Bar (2023), and Puff Bar (2022) e-cigarettes. In 2023, 333 respondents (1.5% of all youth) reported any past-30-day use of Vuse e-cigarettes, with 134 (0.6% of all youth) reporting Vuse as their only or usual brand. Among these 134 only or usual brand users, 84 (0.3% of all youth) provided responses for device type and flavors used that were consistent with use of Vuse. Past-30-day use of JUUL e-cigarettes was reported by 237 respondents (1.2% of all youth), with 42 (0.3% of all youth) reporting JUUL as their only or usual brand. Among these 42 only or usual brand users, 3 (< 0.1% of all youth) provided responses for device type and flavors used that were consistent with use of JUUL. For Elf Bar e-cigarettes, 839 respondents (4.2% of all youth) reported past-30-day use, with 478 (2.3% of all youth) reporting Elf Bar as their only or usual brand. Among these 478 only or usual brand users, 392 (2.0% of all youth) provided responses for device type that were consistent with use of Elf Bar (flavors could not be validly assessed). Analyses of the 2022 NYTS data showed similarly low levels of consistency in reporting for Vuse, JUUL, and Puff Bar e-cigarettes. Thus, substantial proportions of youth in both survey years provided responses for device type used most often and flavors used during the past 30 days that were not consistent with the reported brand used. These findings raise significant concerns regarding the accuracy of the brand-specific prevalence estimates derived from the NYTS data, especially given the weight that the FDA places on these data during its regulatory decision-making.